MENYINGKAP LATENSI EKSOTIK CANDI SUKUH MELALUI MEDIA FOTOGRAFI - Muji Soewasta (Ornamen, 2014)
The presence of photographic technology is, of course, born to hunt objectivity because its capability topicture a visual reality with high precision level. In addition, photography as a very useful image emission inrepresenting a visual reality. Further, photography is not only a representation of a visual object it reproduces,but it also contains a message. It is said that photography is also message shaped by emission resourceand transmission channel. Accordingly, it occupies a position in which a photography technology is expectedto be able to reveal shadow of mystery shrouded the presence of Sukuh Temple.Keywords: high precision, visual reality, covered mysteryÂ